Caring Confrontation Terhadap Perilaku Anti Sosial - Astrid Lingkan Mandas; Irrene C Wayong (Journal Of Psychology humanlight, 2020)
Caring confrontation is defined as a method for presenting clients with ways of looking at themselves of which they may not yet be aware, without losing the respect for each person's inner experience which is essential to a client-centered/experiential approach to therapy. In this case, the subject could gain comprehension of the forms of anti-social behavior that he has not been aware of. The focus of this study is to examine the effect of caring confrontation on anti-social behavior. The implementation of caring confrontation to the subject shows a decrease in anti-social behavior towards the subject. Before the implementation of caring confrontation, subject was often involved in conflicts with schoolmates both verbally and physically, often lied and was manipulative, refused to be advised. After implementation, subject no longer involved into conflict with classmates or schoolmates, opened up to advice and suggestions from his friends, begun to mingle and be accepted by classmates and schoolmates. For other researchers, during the implementation of caring confrontation, the researcher should control other variables such as family so that the implementation of caring confrontation can have a maximum effect. This study used a single-case experimental method. The sample of this research is a student who has anti-social behavior at SMP Lentera Harapan in Tomohon.